Histone deacetylase 2-dependent ventricular electrical remodeling in a porcine model of early heart failure - Syren, Pascal; Rahm, Ann-Kathrin; Schweizer, Patrick Alexander; Bruehl, Claus; Katus, Hugo; Frey, Norbert; Thomas, Dierk; Lugenbiel, Patrick (Life sciences, 2021)
Aims - Heart failure (HF) is linked to electrical remodeling that promotes ventricular arrhythmias. Underlying molecular signaling is insufficiently understood, in particular concerning patients with early disease stages. Previous observations suggest a key role for epigenetic mechanisms in cardiac remodeling processes. We hypothesized that histone deacetylases (HDACs) 1 and 2 contribute to cellular electrophysiological dysregulation in ventricular cardiomyocytes during HF development. - Materials and methods - HDAC and ion channel expression was quantified in a porcine model of early HF induced by short-term atrial tachypacing, resulting in atrial fibrillation with rapid ventricular rate response. Anti-Hdac1 and anti-Hdac2 siRNA treatment was employed in neonatal murine cardiomyocytes (NMCM) to study effects of HDACs on ion channel mRNA expression and action potential duration (APD). - Key findings - Early HF was characterized by mild reduction of left ventricular ejection fraction, prolonged QTc intervals, and increased ventricular effective refractory periods. Delayed repolarization was linked to significant downregulation of HDAC2 in left ventricular (LV) tissue. In addition, there was a tendency towards reduced transcript expression of KCNJ2/Kir2.1 K+ channels. In NMCM, knock-down of Hdac2 recapitulated AP prolongation. Finally, siRNA-mediated suppression of Hdac2 reduced Kcnh2/Kv11.1 K+ channel expression. - Significance - Suppression of HDAC2 is linked to ventricular electrical remodeling of APD and ion channel expression in early stages of heart failure. This previously unrecognized mechanism may serve as basis for future approaches to prevention and treatment of ventricular arrhythmias.